Advances in breast cancer diagnosis: a comprehensive review of imaging, biosensors, and emerging wearable technologies - Khan, Abdul Qadeer; Touseeq, Manahil; Rehman, Sara; Tahir, Maria; Ashfaq, Malaika; Jaffar, Emaan; Abbasi, Saadullah Farooq (Frontiers in Oncology, 2025)
Breast cancer has been the most frequent diagnosed cancer and the leading cause of cancer-related deaths among women worldwide, mainly due to delayed detection. Early diagnosis significantly improves prognosis and long-term survival rates. Various techniques, including imaging, sensors, and molecular biotechnology, have been developed to facilitate early detection. This review provides a comprehensive analysis of these diagnostic techniques, emphasizing precision, patient comfort, and cost-effectiveness. Additionally, it explores the emerging role of wearable technologies, such as smart bras and real-time monitoring devices, in revolutionizing breast cancer detection. The review concludes by discussing the limitations of current diagnostic methods and proposing future directions for enhancing early detection and improving patient outcomes.